Possibilities of application CAPM to Polish Stock Exchange market with help of implied market risk premium - Siewierska, Agnieszka (My University, 2007)
The main purpose of the work is to show that traditional method of estimating MRP, with help of historical data for Polish stock market, is pointless when it comes to accurate results and to propose alternative way to obtain it through Dividend Discount Model (DDM). Looking at many researches gathered especially by American scientists we may say that the market risk premium based on historical data is not applicable to Polish stock exchange market as well as to other emerging markets. To inspect market risk premium we need to use Dividend Discount Model so as to receive cost of equity for the equivalent of the market and then Capital Asset Pricing Model for a premium itself. The work is divided into 4 chapters. First chapter defines portfolio theory and the background of Capital Asset Pricing Model. The second one discusses in details market risk premium as a central component of CAPM and the most questionable factor, as well as the ways of receiving it. The third chapter shows MRP results prepared and published by the financial scientists for US well-developed market. The fourth chapter is the comparison between traditional and alternative way of receiving MRP for Polish stock exchange market.
Możliwości aplikacji metodologii CAPM na polskim rynku kapitałowym
Keywords: akcje; ryzyko kredytowe; ryzyko inwestycyjne